Evaluation of the influence of varying electrode materials within the thermo-crimping process - Spreng, Simon; Gläßel, Tobias; Hoetzel, Stefan; Schäfer, Heiko; Wunder, David; Franke, Jörg (2015 5th International Conference on Electric Drives Production, EDPC 2015 - Proceedings, 2015)
In the field of electric drives manufacturing, the thermo-crimping process is one major technology to join insulated copper wires with belonging current carrying parts. However, due to its operating principle, this technology has to be associated with strong disadvantages e.g. the excessive tool attrition leading to an immoderate amount of maintenance operations. For this reason, this paper focuses on the investigation of varying crimping electrode materials, whereas the objectives product quality, tool attrition and process energy are analyzed.
CRIS-Team Scopus Importer:2023-03-07
Keywords: crimping tool; electric drives manufacturing; joining; thermo-crimping